EFEKTIFITAS LAPORAN HASIL TEMUAN PEMERIKSAAN DALAM MEWUJUDKAN REFORMASI TRANPARANSI FISKAL DAN AKUNTABILITAS SEKTOR PUBLIK (2001-2008) DI INDONESIA - Septiana Dwiputrianti (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2008)
This paper examines and develops the criteria to measure the effectiveness of government auditing reports to enhance the transparency and public accountability from international literatures related to public administration and government auditing. The criteria can be divided into 2 (two) parts, namely: criteria related to information in the audit reports and criteria related toacting on information in the audit reports. The first part consists of criteria related to the quality of information and the audit reports content. The second part consists of criteria related to communication of audit report information and acting on audit information. The research employed case study approach combining qualitative and quantitative methods in Indonesia. The studysurveyed and interviewed key informants including the management of the audit institutions, government auditors, the audited entities (local and central governments) and the Members of Parliament. By examining the reformation legal system for government auditing and comparing this with the best practices from the auditing literatures that formulated in criteria of governmentauditing, the study shows that the Indonesian government auditing has not completely addressed the real needs of public accountability and transparency during this reformation era. This study argues that follow up of the audit findings are the major criteria in terms of acting on information. The study recommends a more effective strategy should be adopted to develop profesionalism andintegrity and to improve qualifications of auditors with different educational background, through education, training and development to move from financial auditing to performance auditing in the future. In addition, increasing audit resources in the local regions is necessary. The last recommendation is to provide better communication and discussion about implementing auditrecommendations and following-up audit reports.